2016
DOI: 10.1074/jbc.m116.718783
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Progression Locus 2 (Tpl2) Activates the Mammalian Target of Rapamycin (mTOR) Pathway, Inhibits Forkhead Box P3 (FoxP3) Expression, and Limits Regulatory T Cell (Treg) Immunosuppressive Functions

Abstract: The serine/threonine kinase tumor progression locus 2 (Tpl2, also known as Map3k8/Cot) is a potent inflammatory mediator that drives the production of TNF␣, IL-1␤, and IFN␥. We previously demonstrated that Tpl2 regulates T cell receptor (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 65 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…The immune-regulatory function of Tpl2 is largely attributed to its activation of the MEK/ERK pathway in toll-like receptor (TLR), interleukin-1 receptor (IL-1R), or tumor necrosis factor receptor (TNFR) signaling (34, 35). In addition, Tpl2 also modulate the activation of p38, JNK, protein kinase B, and mammalian target of rapamycin in a context-dependent manner (25, 36). We previously found that Tpl2 functions in astrocytes to mediate IL-17A-induced chemokine ( Cxcl1/2 ) expression through promoting TAK1 phosphorylation and its downstream NF-κB, p38, and JNK activation, whereas ERK activation is not affected (24).…”
Section: Discussionmentioning
confidence: 99%
“…The immune-regulatory function of Tpl2 is largely attributed to its activation of the MEK/ERK pathway in toll-like receptor (TLR), interleukin-1 receptor (IL-1R), or tumor necrosis factor receptor (TNFR) signaling (34, 35). In addition, Tpl2 also modulate the activation of p38, JNK, protein kinase B, and mammalian target of rapamycin in a context-dependent manner (25, 36). We previously found that Tpl2 functions in astrocytes to mediate IL-17A-induced chemokine ( Cxcl1/2 ) expression through promoting TAK1 phosphorylation and its downstream NF-κB, p38, and JNK activation, whereas ERK activation is not affected (24).…”
Section: Discussionmentioning
confidence: 99%
“…9 T. gondii ESA could diminish the percentage of CD4 + CD25 + Foxp3 + in spleen and inhibit Foxp3 in the maternal-fetal interface. 9 T. gondii ESA could diminish the percentage of CD4 + CD25 + Foxp3 + in spleen and inhibit Foxp3 in the maternal-fetal interface.…”
Section: Introductionmentioning
confidence: 93%
“…Transcription factor forkhead box p3 (Foxp3) mainly modulates the differentiation and functional roles in Tregs . T. gondii ESA could diminish the percentage of CD4 + CD25 + Foxp3 + in spleen and inhibit Foxp3 in the maternal‐fetal interface .…”
Section: Introductionmentioning
confidence: 99%
“…For example, MAP3K8 links IL-17 receptor signaling to TAK1 activation, which leads to increased JNK, p38, and NFκB activity in Th17 cells, promoting autoimmune neuroinflammation [81,82]. Moreover, MAP3K8 activity in T cells limits regulatory T cell (Treg) function by inhibiting FoxP3 expression and lowering production of the immunosuppressive cytokines IL-10 and cytotoxic T lymphocyte-associated protein 4 (CTLA-4) [83]. In addition, TNF-α plays a pivotal role in a variety of autoimmune diseases, causing sustained inflammation and tissue damage [84].…”
Section: Discussionmentioning
confidence: 99%